1993
DOI: 10.2307/2061840
|View full text |Cite
|
Sign up to set email alerts
|

Locational returns to human capital: Minority access to suburban community resources

Abstract: The suburbanization of racial and ethnic minorities is analyzed in terms of the locational resources provided by their communities of residence. In suburbs in the New York CMSA, non-Hispanic whites and Asians, on average, live in communities with higher average socioeconomic status, while Hispanics and blacks live in the less desirable suburbs. Models predicting suburban socioeconomic status for each racial/ethnic group show that whites and Hispanics receive consistent returns on income, acculturation, and fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
312
0
5

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(327 citation statements)
references
References 22 publications
10
312
0
5
Order By: Relevance
“…This is in line with the strong version of the stratification theory (Logan and Alba, 1993), which states that the locational returns of income are relatively low for (stigmatised) minority groups.…”
Section: Neighbourhood Ethnic Compositionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is in line with the strong version of the stratification theory (Logan and Alba, 1993), which states that the locational returns of income are relatively low for (stigmatised) minority groups.…”
Section: Neighbourhood Ethnic Compositionsupporting
confidence: 85%
“…These studies have an important limitation: they generally characterise neighbourhoods based on a limited number of characteristics (Hedman et al, 2011). Studies typically model whether or not households move into a poor neighbourhood (Clark et al, 2006;Logan and Alba, 1993), or into a minority-concentration neighbourhood or not (Brama, 2006;Clark and Ledwith, 2007;Doff, 2010;South and Crowder, 1998). However, in reality, the selection of a neighbourhood will depend on multiple neighbourhood characteristics that are assessed simultaneously and in combination (Hedman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms that bring about the dispersion of ethnic groups are acculturation and socioeconomic mobility (Charles, 2003;Logan and Alba, 1993;Massey, 1985). Acculturation is the gradual acquisition of the language, norms, and values of the host community (Gordon, 1964).…”
Section: How Can Segregation Processes Be Explained?mentioning
confidence: 99%
“…Racial differences in housing values and intergenerational wealth transfers have also been linked to racial differences in human capital (Edin, 2001;Logan & Alba, 1993) and social capital (Astone, Nathanson, Schoen, & Kim, 1999;Coleman, 1988). Non-whites have lower levels of education, occupational prestige and income (Grodsky & Pager, 2001;McCall, 2001) and weaker social ties to networks and institutions that assist in the process of asset accumulation compared to whites.…”
Section: A Critical Review Of the Sociology Of Race And Wealthmentioning
confidence: 99%
“…Researchers have also shown that racial minorities often times have higher unemployment rates, lower educational rates, are less likely than to marry when compared with whites and that racial differences in home ownership is an outcome of those differences (Logan & Alba, 1993). Moreover, research has shown that racial minorities are less likely to have access to professional occupations and have relatively lower incomes (Levy & Richard, 1991).…”
Section: Business Income As a Determinant Of Asset Ownership?mentioning
confidence: 99%